Stipulation of rights in the practice of Nikah Al-Khitbah according to the fuqaha’ and the Islamic family law in Malaysia = Penetapan syarat di dalam amalan Nikah Khitbah menurut fuqaha’ dan undang-undang keluarga Islam di Malaysia - Sitiris, Miszairi; Mat Jubri@Shamsuddin, Mustafa; Awang Hamat, Mohd Afandi (IIUM Press, 2020)
Nikahal-khitbah or popularly known as nikah gantung became a choice of a handful of teenagers especially among university students in Malaysia due to financial constraints and educational reason. Such type of wedding practice raises a number of questions related to juristic issues. This is because the practice of Nikahal-khitbah involves establishing some limitation of rights that violate the purpose or intent of marriage. Among others, the spouses agree to defer some of their rights such as declining the right of nafaqah and the right of sexual intercourse which are against the original purpose (muqtada aqd) of marriage contract. This paper aims to study the opinions of jurists (Fuqaha) regarding such limitation or agreement in marriage contract and their validity according to the Islamic Family Law in Malaysia. This paper relies on analytical study in discussing the opinions of the Fuqaha’ and understanding the legal texts of the law related to the matter. This study found that marriage practice through nikah al-khitbah is valid according to the majority views of FuqahÉ’. Islamic family laws in Malaysia do not deny the validity of such marriage practices although there are some legal effects on the limitation of marriage rights.